(untitled) (Journal of Pharmaceutical Negative Results, 2023)
At the beginning of the Covid-19 pandemic, the service health experience declines healthcare that happens in almost all types of health service in Indonesia, both provided by primary and advanced healthcare facilities. This study aims to analyze factors of utilization service health in patients with hypertension in the Community Health Centers (Puskesmas) Antang. This study uses a quantitative method with a cross-sectional approach. The total sample of as many as 160 participants with the technique taking purposive sampling, whatever data analysis using chi-square and multiple logistic regression test. This study is conducted at the Puskesmas Antang, Makassar City. Research results are known there is a relationship between age (p=0.000), health insurance (p=0.000), and the perception of health-sick (p=0.001) to utilization service health in patients with hypertension. As for the type gender (p=0.298), an education level (p=0.839), occupation (p=0.249), length of suffering (p=0.686), and time wait service (p=0.703), there is no relationship to utilization service health in patients with hypertension. Based on multiple logistic regression test results, health insurance is the most influential factor to utilization service health in patients with hypertension, with a value of B=2.151 (95% CI 3.425-21.564). The expected results of the study are to become the source reference to influencing factors of healthcare utilization in patients with hypertension.